277 Gynaefellow': a new online multi-media resource for gynae-oncology & gynaecology surgery training. (13th November 2020) - Alazzam, M; Antoci, A; Addley, S
Abstract : Study Objective: To study the adoption of new innovative online multimedia educational resource aimed to provide focused surgical and clinical training Design: Free and open access innovative multimedia platform available as web and App formats. Descriptive analysis to study users' behaviours using the online advanced analytics Setting: A new innovative online multimedia educational platform called 'GynaeFellow'; website: www.gynaefellow.com App: (IOS) https://apps.apple.com/gb/app/gynaefellow/id1494635066, (Android) https://play.google.com/store/apps/details? id=com.gynaefellow.app&hl=en_GB Focused peer–reviewed free access online surgical videos provided on the App and reading material offered through the website Participants: All health professionals who work or interested in gynaecology No geographical restrictions Interventions: High quality laparoscopic and open surgical videos deconstructed into simple bite-size and easy-to-follow building blocks to develop surgical knowledge and confidence. Supporting 2–5 minutes focused read resources on the website to consolidate the clinical experience and decision-making knowledge. Measurement: We used the following measurement to assess the adoption of the new platform; Users retention and engagement Multimedia analytics Users feedback Results: The rate of adoption increased by over 100% on a weekly basis and platform was downloaded in over 70 countries within 2 months of release. > 5 K minutes of videos were viewed within 6 weeks of release Conclusion: GynaeFellow provides high quality, easy-to-follow surgical videos illustrating anatomy planes that are readily available and can be repeatedly accessed by the keen gynaecologists providing a self-directed learning experience that can be translated into practice in the operating room – increasing patient's safety and enhancing each operating opportunity. There is a universal adoption to innovative educational platforms.